GLYOXYLATE METABOLISM IN GROWTH AND SPORULATION OF BACILLUS CEREUS - Megraw, Robert E. (1964)
Megraw, Robert E. (Iowa State University, Ames), and Russell J. Beers. Glyoxylate metabolism in growth and sporulation of Bacillus cereus. J. Bacteriol. 87:1087–1093. 1964.—Isocitrate lyase and malate synthetase were found in cell-free extracts of Bacillus cereus T. The patterns of synthesis of enzymes of the glyoxylic acid cycle were dependent upon the medium in which the organism was grown. Cells grown in acetate or in an acetate precursor, such as glucose, produced enzymes of the glyoxylic acid cycle in greatly diminished quantities, as compared with cells grown in media containing glutamate or yeast extract as principal carbon sources. Glutamate-grown cells had high isocitrate lyase activity but very low malate synthetase activity. Glyoxylate produced in this situation is metabolized by alternate pathways: conversion to tartronic semialdehyde and the latter to glyceric acid, thus providing evidence for a glycerate pathway; and reduction to glycolate (the reverse of this reaction was present at a low rate). Enzymatic activity of the glyoxylic acid cycle declines at the point where sporogenesis begins, indicating a metabolic shift for the synthesis of spore material.